PENGARUH GUIDED DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V UPTD SD NEGERI 1224405 - Dewi Sofianty Sipayung; Radode Kristianto Simarmata; Hendra Simanjuntak (JOURNAL SAINS STUDENT RESEARCH, 2024)
Thils resealrch alilms to determilne the effect of the Guilded Dilscovery Lealrnilng Model on clalss V lealrnilng outcomes iln malthemaltilcs lealrnilng alt Stalte Elementalry School 124405. The type of resealrch used ils qualntiltaltilve resealrch wilth al pre-experilmentall desilgn usilng al One Group Desilgn Pretest-Posttest desilgn. The populaltilon of thils study wals alll filfth gralde students wilth al totall of 23 students. The daltal collectilon technilque used iln thils resealrch ils multilple choilce (pretest-posttest). The results of daltal alnallysils of clalss V student lealrnilng outcomes obtalilned were aln alveralge pretest score of 50.35 alnd daltal on student lealrnilng outcomes ilncrealsed obtalilned from aln alveralge posttest score of 81.91. The results of thils resealrch alre strengthened by the results of the t-test whilch shows thalt the alveralge vallue of the t-test score ils 10.724. so ilt caln be concluded thalt valrilalble X (Guilded Dilscovery Lealrnilng lealrnilng model) hals al silgnilfilcalnt effect on valrilalble Y (Student Lealrnilng Outcomes).